Pelaksanaan Strategi Pembelajaran Experiential Learning Era New Normal Pada Mata Pelajaran Akidah Akhlak Di MTSN 6 Agam Kab. Agam - Indah Oktaviani; Wedra Aprison (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
In the Experiential Learning learning strategy there are four stages of implementation consisting of concrete experience, observation and reflection, conceptualization, and active experience. However, it is suspected that in reality there are two things that have not been implemented properly, namely concrete experience, observation and reflection. The purpose of this study is to describe the implementation of the New Normal Era of Experiential Learning Strategy on Akidah Akhlak Subjects in class VIII 5. The type of research used is qualitative in the form of descriptive. Data collection techniques are observation, interviews, and documentation. This study used primary and secondary informants consisting of teachers, students, and school principals. In this study also uses data analysis techniques Miles and Huberman version which consists of data reduction, data presentation, and drawing conclusions.The results showed that the Experiential Learning strategy is an activity carried out by teachers and students to realize teaching and learning activities that construct knowledge through the transformation of experience, which involves students directly in learning. This strategy consists of 4 implementations namely concrete experience, observation and reflection, conceptualization, and active experience. Based on research in the field, teachers at MTsN 6 Agam have carried out learning with Experiential Learning strategies as well as possible in this new normal era in the subjects of aqidah morality class VIII 5. Teachers have carried out well the stages of concrete experience and active experience, but there are two implementations that need to be implemented. not run well in the classroom, namely observation, reflection and conceptualization.